Prognostic Predictors of Visual Outcome in Open Globe Injury: Emphasis on Facial CT Findings - Bodanapally, U.K.; Addis, H.; Dreizin, D.; Reddy, A.K.; Margo, J.A.; Archer-Arroyo, K.L.; Feldman, S.; Saboury, B.; Sudini, K.; Saeedi, O. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: The present prognostic models for open globe injuries have a limited ability to predict visual outcome before a comprehensive ophthalmologic examination or operation because they depend on the data derived from the ophthalmologic examination and intraoperative findings. The purpose of our study was to determine the specific CT and preoperative clinical data that can predict the prognosis of open globe injury.MATERIALS AND METHODS: We analyzed the relationship of 29 variables derived from clinical and CT data from 97 globe injuries with visual acuity at 1 month. A prediction model was derived from 49 globe injuries by regression analysis, followed by receiver operating characteristic curve analysis of the best CT predictor.RESULTS: Four variables with significance on a regression model were the following: posterior segment hemorrhage (β = −0.93, P < .0001), presenting visual acuity (β = 0.28, P = .042), orbital emphysema (β = 0.46, P = .0018), and complex facial fracture (β = −0.43, P = .009). Receiver operating characteristic analysis of the posterior segment hemorrhage predicted profound vision loss (light perception or no light perception) with an area under the curve of 0.97. The receiver operating characteristic table indicated that grade III posterior segment hemorrhage has a strong positive predictive value of 100% for profound vision loss. On the other hand, the absence of posterior segment hemorrhage has a strong positive predictive value of 93% for mild-to-severe vision loss (visual acuity better than light perception).CONCLUSIONS: Radiologists, with the help of CT and preoperative clinical data, can predict visual acuity after open globe injury.IOPintraocular pressureLPlight perceptionlogMARlogarithm of the minimum angle of resolutionNLPno light perceptionPPVpositive predictive valueRAPDrelative afferent pupillary defectVAvisual acuity